Atherogenic index of plasma and the risk of rapid progression of coronary atherosclerosis beyond traditional risk factors. (May 2021) - Won, Ki-Bum; Heo, Ran; Park, Hyung-Bok; Lee, Byoung Kwon; Lin, Fay Y.; Hadamitzky, Martin; Kim, Yong-Jin; Sung, Ji Min; Conte, Edoardo; Andreini, Daniele; Pontone, Gianluca; Budoff, Matthew J.; et al.
Abstract: Background and aims: The atherogenic index of plasma (AIP) has been suggested as a marker of plasma atherogenicity. This study aimed to assess the association between AIP and the rapid progression of coronary atherosclerosis using serial coronary computed tomography angiography (CCTA). Methods: A total of 1488 adults (60.9 ± 9.2 years, 58.9% male) who underwent serial CCTA with a median inter-scan period of 3.4 years were included. AIP was defined as the base 10 logarithm of the ratio of the concentrations of triglyceride to high-density lipoprotein cholesterol. Rapid plaque progression (RPP) was defined as the change of percentage atheroma volume (PAV) ≥1.0%/year. All participants were divided into three groups based on AIP tertiles. Results: Baseline total PAV (median [interquartile range (IQR)]) (%) (group I [lowest]: 1.91 [0.00, 6.21] vs. group II: 2.82 [0.27, 8.83] vs. group III [highest]: 2.70 [0.41, 7.50]), the annual change of total PAV (median [IQR]) (%/year) (group I: 0.27 [0.00, 0.81] vs. group II: 0.37 [0.04, 1.11] vs. group III: 0.45 [0.06, 1.25]), and the incidence of RPP (group I: 19.7% vs. group II: 27.3% vs. group III: 31.4%) were significantly different among AIP tertiles (all p  < 0.05). In multiple logistic regression analysis, the risk of RPP was increased in group III (odds ratio: 1.52, 95% confidence interval: 1.02–2.26; p  = 0.042) compared to group I after adjusting for clinical factors and baseline total PAV. Conclusions: Based on serial CCTA findings, AIP is an independent predictive marker for RPP beyond traditional risk factors. Graphical abstract: Image 1 Highlights: The association of atherogenic index of plasma (AIP) with the rapid progression of coronary atherosclerosis is uncertain. This study identified that high AIP levels were independently associated with an increased risk of rapid plaque progression. This finding suggests that AIP has additive values for cardiovascular risk stratification.